Diseño de Librería con Enfoque Didáctico para Control de Robots Manipuladores en Sistemas Embebidos - Garcia Luna, Francesco Jose (2019)
In the present paper, a computational tool for position/orientation control of a n-degrees of freedom manipulator robot is shown. The tool contains the necessary functions in order to calculate the robot’s forward kinematics by means of the rotation/translation homogeneous transformation matrices, the linear/angular velocities Jacobian matrices, and the position/orientation control by means of a PID scheme. The results using the library in a 3 rotational degrees of freedom robot manipulator set-point control is shown, where the final effector’s pose converges at the reference in finite time.